Identification of sodium homeostasis genes in Camelus bactrianus by whole transcriptome sequencing - Dong Zhang; Jing Pan; Chunxia Liu; Fanhua Meng; Yanru Zhang; Junwei Cao; Yu Cao; Huanmin Zhou (FEBS Open Bio, 2022)
Salt dietary intake is tightly coupled to human health, and excessive sodium can cause strokes and cardiovascular diseases. Research into the renal medulla of camels exhibiting high salt resistance may aid identification of the mechanisms governing resistance to high salinity. In this study, we used RNA sequencing (RNA‐seq) to show that in the renal medulla of camels under salt stress, 22 mRNAs, 2 long noncoding RNAs (lncRNAs), and 31 microRNAs (miRNAs) exhibited differential expression compared with the free salt‐intake diet group. Using fluorescence in situ hybridization and dual‐luciferase reporter assays, we demonstrated that the lncRNA LNC003834 can bind miRNA‐34a and thereby relieve suppression of the salt‐absorption‐inhibiting SLC14A1 mRNA from miRNA‐34a, suggesting that the above lncRNA‐miRNA‐mRNA act as competing endogenous RNAs (ceRNAs). We subsequently performed short hairpin RNA and small RNA interference and reactive oxygen species (ROS) detection assays to show that SLC6A1, PCBP2, and PEX5L can improve the antioxidation capacity of renal medulla cells of camel by decreasing ROS levels. Our data suggest that camels achieve sodium homeostasis through regulating the expression of salt‐reabsorption‐related genes in the renal medulla, and this involves ceRNAs (SLC14A1 mRNA, LNC003834, and miRNA‐34a) and antioxidant genes (SLC6A1, PCBP2, and PEX5L). These data may assist in the development of treatments for diseases induced by high salt diets.